Microstructural evolution of heat-treated 316L stainless steel using various etchants - Moumakwe Molebogeng; Arthur Nana K.K; Poopola Abimbola P.I; Raji Sadiq A. (MATEC Web of Conferences)
The rapid heating and cooling cycles inherent to laser additive manufacturing result in the accumulation of high residual stress magnitudes that may have an adverse effect on the material's mechanical properties. Post-processing heat treatment has been suggested to mitigate the problems associated with residual stress build-up and heterogeneous microstructure that results from localized heating and rapid solidification. This study investigates the effect of post-processing heat treatment of additively manufactured 316L stainless steel impellers to customize the treatment for optimal microstructure and mechanical performance. The samples were stress-relieved and solution-treated to homogenize the microstructure. From the results, it was observed that heat treatment substantially decreased the microhardness of the as-built specimen. The microhardness was reduced by 10% when stress relief was applied at 600ºC while showing a reduction of 28% at an annealing temperature of 1150ºC. Furthermore, the potassium in water etchant revealed carbide precipitates more pronounced and visible in the solution-treated specimens than in stress-relieved specimens. Similarly, Kallings etchant revealed a heterogeneous microstructure with a laser- generated pattern more visible in the stress-relieved specimen while no apparent pattern was observed in the homogenized specimen.